A Prospective Study of Foreign Bodies in Aero-Digestive Tract at a Tertiary Care Center in Eastern Nepal - Sah, Bajrang Prasad; Chhetri, Shyam Thapa; Sah, Shankar Prasad; Paudel, Deepak; Sarraf, Deependra Prasad (Medical Journal of Eastern Nepal, 2022)
Background Aero-digestive tract foreign body (FB) is a common emergency dealt by the otolaryngologists. Airways FB have been a major cause of morbidity and mortality. Management of FB depends on the site of impaction and types of it. The study aimed to find out the incidence, types and complications of FB encountered in aerodigestive tract. Methods A hospital-based prospective study was conducted among the patients with aero digestive FB presented and managed at the department of ENT and HNS from August 2015 to July 2017. A self-designed proforma was used to collect the relevant data. A descriptive analysis was made of the frequency distribution of qualitative variables. The findings were presented as tables and graphs. Results A total of 276 patients were treated for FB in aero-digestive tract and 158 (57.25%) patients were male. 90 (32.6%) cases of FB occurred in age group of 1-10 years. Ninety six cases of foreign body (34.78%) were chicken bone followed by other bone (20.65%) and coin (18.12%). All cases of coin were seen in children <13 years old and disc Battery in children <10 years old. Out of 276 cases of foreign bodies, 254 (92.03%) were in upper digestive tract and 22 (7.97%) in airways. About 140 (50.72%) were in cricopharynx, 103 (37.32%) in esophagus and 11 (3.99%) in other sites in intestine.Complications were seen in 10 (3.62%) cases and retropharyngeal abscess was the most common (60%). Conclusion Cricopharynx was the most common site of FB lodgment in the digestive tract. Right main bronchus was the commonest site of lodgment of inhaled FB. Seeds, nuts, whistles, small toys were commonly seen obstructing the airway in children. They need to be trained not to keep these things in the mouth.